Methylated Ellagic Acid Glycosides from Eucalpytus rostrata - Michael, H.N.; Salib, J.Y.; Ishak, M.S. (Asian Journal of Chemistry, 2010)
Leaves of Eucalyptus rostrata contained two new natural glycosides:3,3',4-tri-O-methylellagic acid-4'-O-β-D-galactoside (1) and 3',3',4-tri-Omethylellagicacid-4' -O-mannosylglucoside (2). The known glycoside3',3',4-tri-O-methylellagic acid-4'-O-β-D-glucoside (3) in addition to thepolyphenolic constituents, namely, 3,3',4-tri-O-methylellagic acid (4);3-3'-di-O-methylellagic acid (5); ellagic (6) and gallic (7) acids have alsobeen isolated. The structures of all the isolated components were determinedby both chemical and spectral analyses.